An Analysis of User Satisfaction with TransJakarta Bus Stop Infrastructure Quality in East Jakarta - Mohamad Kamyah; Alizar Alizar (Jurnal Teknik dan Science, 2025)
This study aims to analyze the extent to which the quality of bus stop infrastructure influences the satisfaction level of Transjakarta users. The research focuses on three key aspects: comfort, accessibility, and safety of the bus stops, which are considered essential elements in shaping public transportation user experience. Data collection was conducted at several bus stops representing various infrastructure conditions across the Jakarta area. A total of 160 respondents, all regular users of Transjakarta, participated in the study. The data analysis seeks to identify the degree of influence each variable has on overall user satisfaction